A numerical investigation for tangent hyperbolic hybrid nanofluid transportation across Riga wedge - Yahya, Asmat Ullah (2022)
This communication presents an enhancement of heat transportation of tangent hyperbolic nanofluid comprised of silver / Gasoline oil and silver (Formula presented.) /Gasoline oil. The flow of fluid is caused by the stretching Riga wedge. The leading nonlinear coupled differential formulation is transmuted into ordinary differential form with the utilization of similarity transform. Numerical findings are yielded by hiring the Runge–Kutta method and shooting procedure coded in a MATLAB script. The computational run is carried out to explore the influence of notable parameters on skin friction, velocity, local heat transfer rate, and temperature of the fluid. The range of the parameters are taken arbitrarily as (Formula presented.), (Formula presented.), (Formula presented.), (Formula presented.) and (Formula presented.), etc. It is noticed that flow accelerates with modified Hartman number and Weissenberg number. The temperature is incremented directly with heat source strength and Biot number. The velocity of mono nanofluid (Ag/Gasoline) is slow as than that of hybrid nanofluid but the temperature behaves reciprocally.